ASSESSING THE CONFLICT RESOLUTION POTENTIAL OF NEGOTIATIONS IN THE KOSOVO SERBIA CONFLICT - Etlent DORDA; Reina ZENELAJ SHEHI; Ada CARA (Annals of the "Ovidius" University of Constanţa. Political Science Series)
This paper focuses on the analysis of the role of the negotiation process towards the conflict resolution between Kosovo and Serbia after Kosovo’s proclamation of independence. The main research question it addresses is: “To what extent has the negotiation process made an impact and offered an official solution to the conflict between Kosovo and Serbia?” The documents consulted for all rounds of negotiations completed from 2011 until the end of 2020 show that both countries have discussed mostly tangible and technical issues like free movement, economic development, minority rights, and political cooperation. During the dialogue period, Kosovo and Serbia signed numerous agreements and discussed a wide array of issues, achieving resolution on several technical matters. Despite the signing of thirty-three agreements, the pace of progress in the negotiation process has slowed in recent years. Analysis of these agreements indicates that while technical issues have been addressed, critical matters such as territoriality, sovereignty, and the recognition of Kosovo’s independence have remained unresolved since the end of 2019, continuing into 2024. The paper concludes by recommending the continuation of negotiations, even at a technical level, improving government communication and transparency to avoid usual ambiguities. The success of negotiations would significantly benefit the Balkan region’s development and progress.